EFFECT OF CHEMICAL ACTIVATION TREATMENTS ON PARTHENOGENETIC DEVELOPMENT OF IN VITRO MATURED BUFFALO OOCYTES - REENA, D; BALASUBRAMANIAN, S; DEVANATHAN, T G (The Indian Journal of Animal Reproduction, 2023)
This study was designed to investigate the effect of chemical activation treatments on parthenogenetic development of in vitro matured fresh (24 h) and aged (30 h) buffalo oocytes. Six trials were conducted each with control, ethanol and ionomycin activation treatments. In control group, none of the oocytes cleaved. In the ethanol activation (EA) group, the cleavage rates of fresh and aged oocytes were 10. 75 ± 3.02 and 21.19 ± 2.24, respectively and there was significant difference (P<0.01) among them. In the ionomycin activation (IA) group, the cleavage rates of fresh and aged oocytes were 18.33 ± 1.89 and 26.13 ± 5.32 per cent, respectively and there was significant difference (P<0.01) among them. No significant difference (P>0.05) between the cleavage rates of fresh and aged activated oocytes with ethanol and ionomycin. It can be concluded that both ethanol and ionomycin can parthenogenetically activate buffalo oocytes and a minimum duration of oocyte maturation interval of 30 h was required for the efficient activation.